Human Genetics as Neo-Genesis Exploring the Pathway to the God in Man - Osai, O. Jason (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
The article embarks on a critique of man’s advancement in human genetic engineering within the context of the creation process from the perspectives of the creation myths as contained in the literatures of Judeo-Christian and Islamic theologies. The author ventures into the perceptions of Hume and Plato on God and the Igbo (Nigeria) cosmogony. He argues that, through the exploits of the painstaking process of genetic engineering, man has commenced exploring the creation course of action, albeit at the rudimentary stages. The creation of man involved not the magic-wand oversimplification contained in the allegories of Genesis; rather, it took the arduous process of scientific experimentation, embryo culturing and other advanced processes that are beyond man’s contemporary level of technological and scientific know-how. This hypothesis is derived from a contemplative scrutiny of the allegories in the Biblical creation myth and the comparatively more explicit Qur’anic account vis-à-vis man’s exploits in human genetic engineering.The article concludes that man has commenced exploring the pathway to the God in him and will, somewhere along the line in the endlessness of eternity, create in his image and likeness.